Postpartum hypertension – an evidence based audit. (16th November 2010) - Anbazhagan, A; Fogarty, P; Hunter, A; Harper, R
Abstract : Postpartum hypertension though common (12%) has no universally accepted guidelines regarding its management resulting in confusion for staff and danger to patients. Aim: To review the current practice in the management of women with postpartum hypertension in two hospitals and their follow-up in the community To draw evidence based protocol for the management of postpartum hypertension. Methods: A retrospective review of the case notes between 2004/2006 at RJMH and Ulster Hospital. Various medications, their doses and the duration of treatment were noted and questionnaire sent to GPs regarding postnatal blood pressure and proteinuria check. A protocol was formulated for the management of these patients based on literature review. Results: 23% of postpartum women at the Ulster Hospital and 31% at the RJMS required treatment with antihypertensives during the postpartum period. There was no uniformity in the management of these women and a wide range of antihypertensives were being used. BP was checked in 92% of the women and proteinuria only in 45% of the women at the postnatal review. Conclusion: Evidence from literature suggests that during the postnatal period antihypertensive agents- atenolol, nifedipine and enalapril should be started and increased in a stepwise fashion as dictated by the blood pressure.